Colditz - The Complete Series Episode 1-28 - Ferguson, Michael; Ritelis, Viktors; Cregeen, Peter; Hamilton, Fred; Henman, Ray; Englander, Adolphe Arthur; MacCallum, David; Neame, Christopher; Wagner, Robert (2 entertain Video, 2010)
The infamous German prisoner of war camp Oflag IVC, better known as Colditz, was supposed to be escape proof and was used by the Germans to imprison renegade British, French, Polish and Dutch prisoners during the Second World War. 'British' in this context includes prisoners from Great Britain, Australia, New Zealand, Canada and Africa as all of these countries made up the British Empire. Based on the memoirs of Colditz Castle escapee Major Pat Reid, who also acted as Technical Adviser to the show, "Colditz" was a psychologically tense and dramatic series which portrayed the many attempted escapes from the castle, and also examined the relationships between the Germans and their prisoners. The show was ahead of its time in that it did not present the Germans as being simply bad. Rather, the Kommandant of Colditz was sympathetically portrayed as being a gentleman with a lot in common with his opposite number, Lieutenant Colonel Preston, head of the British contingent of POW's. There was no overt jingoism in the story. Instead it attempted to show both the German and allied sides of the story, with special emphasis on the pressures which the German Wermacht were under from the Gestapo, who had ambitions to run Colditz themselves. The castle itself takes on a claustrophobic character of its own, with its many passageways, tunnels, barred windows and locked doors. Only with the arrival of the second series of "Colditz" and the advent of the sadistic S.S. Major Mohn was the evil of the Gestapo introduced into the story. [www.tvrage.com]